Synovial sarcoma: A decade of insights from a tertiary referral center - Anupam Lahiri; Himanshu Rohela (Journal of Orthopaedic Reports)
Background: Synovial sarcoma (SS) constitutes approximately 10 % of all sarcomas, primarily affecting younger individuals but found across diverse anatomical sites with a propensity for lung metastases. Objective: This retrospective study aimed to assess clinical characteristics, survival outcomes, and treatment efficacy in 39 patients with synovial sarcoma treated at an Indian tertiary referral center from 2009 to 2019. Methods: Data encompassed demographics, disease features, treatments, and outcomes retrieved from institutional records. Survival analyses included Kaplan-Meier estimates for overall survival (OS), disease-free survival (DFS), local recurrence-free survival (LRFS), and distant metastasis-free survival (DMFS). Results: The cohort, predominantly male (51.3 %) with a median age of 36.4 years, featured tumors mostly deep-seated (82.5 %) and located in extremities (82.1 %). Surgical excision with clear margins was achieved in 97.4 % of cases, supplemented by adjuvant radiotherapy in 74.4 %. Five-year and ten-year OS rates were 57 % and 26.3 %, respectively. Local recurrence occurred in 15.3 % of cases, with 48.7 % developing distant metastases, primarily to the lungs. Factors significantly impacting survival included tumor depth, disease stage, and subcentimeter nodules on chest imaging. Conclusion: This study provides comprehensive insights into synovial sarcoma's clinical profile and treatment outcomes at an Indian tertiary center. Despite aggressive surgical and adjuvant therapies, recurrence rates remain notable, emphasizing the need for advanced therapeutic strategies and prospective studies to optimize patient management and outcomes.